Gamma Knife Surgery for Brain Metastasis from Hepatocellular Carcinoma - Xu, Qingsheng (Public Library of Science, 2014)
OBJECTIVES: The authors evaluated the results of Gamma knife surgery (GKS) for the treatment of metastatic brain tumors from hepatocellular carcinoma (HCC). METHODS AND RESULTS: The authors conducted a retrospective review of the clinical characteristics and treatment outcomes in 14 patients with metastatic brain tumors from HCC who underwent GKS. Twelve (85.7%) patients were male. The mean age of the patients was 53±12 years. There were totally 22 brain metastases in 14 patients and 8 patients (57.1%) presented with a single brain lesion. Intracranial hemorrhages occurred in 13 (59.1%) of the 22 lesions. The mean KPS score was 81±14 (range 50–100). Eleven (78.6%) patients were classified as RTOG RPA Class 2. The mean tumor volume was 8.16±8.15 cm(3) (range 0.59–27.0 cm(3)). The mean marginal dose prescribed was 18.7±3.2 Gy (range 10.0–22.0 Gy). The mean number of shots administered was 10±9 (range 1–27). The median overall survival time after GKS was 5.0±0.93 months (95% CI 3.2–6.8). No complications related to the radiosurgical treatment were identified. Multivariate analysis showed that the total volume of brain metastases, the RTOG RPA class and serum AFP level were significantly correlated with patients’ survival time. CONCLUSIONS: Although survival was extremely poor in patients with brain metastasis (BM) from HCC, GKS was shown to lead to prolongation of the survival time. Accordingly, GKS can be considered as a valuable treatment option for proper patients with HCC BM.